Penerapan Langkah Polya dalam Model Problem Based Instruction untuk Meningkatkan Kemampuan Siswa Menyelesaikan Soal Cerita Persegi Panjang - Rudtin, Nur Afrianti (Jurnal Elektronik Pendidikan Matematika Tadulako, 2013)
The purpose of this research is to obtain a description in the implementation of Polya phase in Problem Based Instruction model which can increase the students’ ability to solving the word problem about rectangular in VII SMP Negeri 7 Palu. Type research is of classroom action research. Plan of this research is based of  Kemmis and Mc. Taggart. Based on the result of the research, learning to use Polya phase in Problem Based Instruction model which can increase the students’ ability to solving the word problem about rectangular in VII SMP Negeri 7 Palu, those are: 1) student’s orientation to the problem; 2) organize student’s to study; 3) guiding individual or group investigation; 4) developing and presenting the work; 5) analyzing and evaluating the problem solving process. Stage of guiding individual or group investigation Polya contains four phase, that is: a) understanding the problem, b) devising plan, c) carrying out the plan, and d) looking back.